Performance and meat quality of native and continental cross steers grazing improved upland pasture or semi-natural rough grazing - Fraser, M.D.; Davies, D.A.; Vale, J.E.; Nute, G.R.; Hallett, K.G.; Richardson, R.I.; Wright, Iain A. (Elsevier, 2009)
There is growing interest in the environmental benefits of grazing by cattle, yet little information is available regarding the levels of production that might be achieved on semi-natural rough grazing (SNRG). The overall aim of this research was to assess the performance of native and ‘improved’ breeds of cattle when grazing grass/clover swards and SNRG in order to explore potential genotype × nutritional environment interactions. This paper reports the findings of three experiments conducted over three years. The first experiment assessed the performance of autumn-born Welsh Black (WB) and Charolais cross (CX) cattle aged approximately 9 months when grazing ryegrass/white clover-dominated improved permanent pasture (PP) and Molinia caerulea-dominated SNRG. Both genotype and pasture type had significant effects on liveweight gain, with growth rates higher for WB steers than CX steers (P < 0.001) and higher on the improved pasture than on the SNRG (P < 0.001). The second experiment was conducted the following summer when the steers were 20 months old and evaluated the effects of breed and pasture type on subsequent finishing performance, carcass composition, meat quality, flavour and fatty acid composition. Genotype had no effect on liveweight gain during the grazing period, but pasture type again had a highly significant effect on growth rate (P < 0.001). Carcass conformation was good and similar for both breeds. Pasture type had a greater effect on fatty acid composition of the meat than did breed. Likewise, genotype had no effect on meat colour or stability, whereas pasture type affected both. Loin steaks from the SNRG-grazed animals had significantly more vitamin E than those from PP-grazed animals (P < 0.001) and this was reflected in lower lipid oxidation (TBARS) after simulated retail display (P < 0.001). The third experiment assessed the performance of spring-born Welsh Black and Limousin cross steers aged 14 months when grazing PP and SNRG. Again only pasture type had a highly significant effect on growth rate (P < 0.001). Measurements made during the first two experiments using automatic behaviour recorders indicated that pasture type influenced grazing behaviour to a greater degree than breed, and sward measurements found no between-breed differences in utilisation of M. caerulea. Overall the results indicate that the type of sward grazed has a greater influence on animal performance and meat quality than breed type when beef cattle are produced in Less Favoured Areas.